Parallel data acquisition of in‐source fragmented glycopeptides to sequence the glycosylation sites of proteins. Issue 11 (9th April 2016) - Zhao, Jingfu; Song, Ehwang; Zhu, Rui; Mechref, Yehia
Abstract : Glycosylation plays important roles in maintaining protein stability and controlling biological processes. In recent years, the correlation between aberrant glycoproteins and many diseases has been reported. Hence, qualitative and quantitative analyses of glycoproteins are necessary to understand physiological processes. LC–MS/MS analysis of glycopeptides is faced with the low glycopeptide signal intensities and low peptide sequence identification. In our study, in‐source fragmentation (ISF) was used in conjunction with LC–MS/MS to facilitate the parallel acquisition of peptide backbone sequence and glycan composition information. In ISF method, the identification of glycosylation sites depended on the detection of Y1 ion (ion of peptide backbone with an N ‐acetylglucosamine attached). To attain dominant Y1 ions, a range of source fragmentation voltages was studied using fetuin. A 45 V ISF voltage was found to be the most efficient voltage for the analysis of glycoproteins. ISF was employed to study the glycosylation sites of three model glycoproteins, including fetuin, α1‐acid glycoprotein and porcine thyroglobulin. The approach was then used to analyze blood serum samples. Y1 ions of glycopeptides in tryptic digests of samples were detected. Y1 ions of glycopeptides with different sialic acid groups are observed at different retention times, representing the various numbers of sialic acid moieties associated with the same peptide backbone sequence. With ISF facilitating the peptide backbone sequencing of glycopeptides, identified peptide sequence coverage was increased. For example, identified fetuin sequence percentage was improved from 39 to 80% in MASCOT database searching compared to conventional CID method. The formation of Y1 ions and oxonium ions in ISF facilitates glycopeptide sequencing and glycan composition identification.